Mixed martial arts unleashed mastering the most effective moves for victory - Dimic, Mickey (McGraw-Hill professional, 2009)
"Mickey Dimic is a great coach and a terrific fighter. "Mixed Martial Arts Unleashed" does an excellent job covering everything MMA beginners need to know to prepare themselves before entering the ring, in addition to providing some knockout tips and drills for advanced fighters."-Carlos Newton, UFC Welterweight World Champion Today, millions the world over are getting fit and fighting hard with mixed martial arts, a lethal combination of kickboxing, judo, boxing, wrestling, and other disciplines. In "Mixed Martial Arts Unleashed," champion and coach Mickey Dimic distills his impressive knowledge to give you dozens of surefire techniques for winning matches.